Analisis Aktivitas Belajar Siswa Kelas XI SMA dalam Pembelajaran Matematika Berbantuan Geogebra antara Pendekatan Laboratorium dan Pendekatan Klasikal - Rudhito, Marcellinus Andy; Iman Santoso, Fransiskus Gatot; Kristanto, Vigih Hery (Widya Warta, 2014)
This research aims to find whether or not there is any difference of students’ study activity in GoeGebra assisted mathematics learning with laboratory approach and that with classical approach on the second-year-students of senior high school. The research is quantitative in nature. It was carried out at SMAN 1 and SMAN 5 Madiun in the semester two of the academic year 2012/2013. The data were collected using non-test method. It was in the form of observation sheets of students’ activity. The sample was obtained applying cluster random sampling technique. The statistical analysis of the data showed that students’ study activity in GoeGebra assisted mathematics learning with laboratory approach was better than thatwith classical approach.